Effectiveness of supreme student government (ssg) officers in their mandated functions: basis for the development of leadership handbook - Barnuevo, Mishell P. (San Miguel, Iriga City: University of Saint Anthony, 2019)
Effectiveness of supreme student government (ssg) officers in their mandated functions: basis for the development of leadership handbook.
Includes bibliographical references.
English
Keywords: Leadership handbook